User perception on urban light rail transit - Phoong, Seuk Yen; Phoong, Seuk Wai; Moghavvemi, Sedigheh; Phoong, Kok Hau (Horizon Research Publishing, 2019)
Public transport is a shared passenger transport service available for public use. Increased population is accompanied by the increased demand for private vehicles. The exponential growth in the number of private vehicles will result in negative impacts such as air pollution, excessive noise, and traffic congestion. Additionally, customers’ perceptions on different aspects include safety, operation or time, comfortableness and cleanness of public transportation that are also essential in affecting their mode of choice when travelling. The public transport that is discussed in this paper is light rail transit. This paper intends to investigate the main purpose of using light rail transit and elucidate the public perspective of the light rail transit via factor analysis and correlation analysis. A questionnaire with five-point Likert scale was designed, and data were randomly selected from 200 light rail transit users in Kuala Lumpur, Malaysia. The results revealed that the majority of the customers use light rail transit to school or university. Moreover, most of the users satisfy with the safety, operation, cost, comfortableness and cleanness of the light rail transit. This can be concluded that light rail transit provides mobility and choice for everyone in the context of efficiency, health and safety, affordability, accessibility, and environmental friendliness. © 2019 by authors, all rights reserved.